Let's solve for x. 6x−2y=2 Step 1: Add 2y to both sides. 6x−2y+2y=2+2y 6x=2y+2 Step 2: Divide both sides by 6. 6x 6 = 2y+2 6 x= 1 3 y+ 1 3 Answer: x= 1 3 y+ 1 3
thats for the first equation.
1/3 y+ 1/3
oh.. thank you!! that was easier than i expected
\[6x - 2y = 2 \\2 + 6x = y\] you can substitute \(2+6x\) for \(y\) in the first equation, since that is what it is you get \[6x-2(2+6x)=2\]
@pokiedokie it might seem easy but that answer is totally wrong
you are solving a system of equations, i.e. where the lines intersect. you are not solving for x and y in one equation which is impossible
do you understand what i wrote above?
yes i do understand a bit of it
can you solve \[6x-2(2+6x)=2\] for \(x\)?
i think so, but i'm still a little confused on where to start in the equation. like as in, do i take care of the parentheses first like in PEMDAS
no it is not arithmetic, it is algebra first use the distributive law to get rid of the parentheses
OH, okay thats what i meant sorry, yikes... so i distributed, is this correct: 6x - 4 + 12x = 2
now combine like terms on the left
oh sorry, no it is not right, but it is close
\[6x - 4 -12x = 2 \] is more like it
oh okay, give me a second to combine
sorry, i'm terrible at math but do you mean combining 6x with 12x or 4 and 2
i mean do \[6x-12x\]
im pretty sure the placement in what i put is wrong but it is x - 4-6x = 2
what is \(6-12\)?
ok so \[6x-12x=-6x\] right?
so you should have \[-6x-4=2\] add \(4\) next
-6x = 6??
and then i just divide
@satellite73 the answer is -1, correct?
thank you so much, sorry for being a pain in the butt!!
no problem btw this makes it "consistent" the fact that you get an answer
noted, thank you very much!